Association between protein feeding and reproductive efficiency in the dairy cow: specific emphasis on protein feeding in Finland - Shingfield, Kevin John; Jokela, Marjatta; Kaustell, Kaisa; Huhtanen, Pekka; Nousiainen, Juha (Agricultural Research Centre of Finland, 1999)
Tässä kirjallisuustutkimuksessa on tarkasteltu valkuaisruokinnan ja hedelmällisyyden välistä yhteyttä lypsylehmillä. Julkaistun aineiston perusteella valkuaisruokinnan vaikutus hedelmällisyyteen vaihtelee. Hedelmällisyyden parametreinä käytettiin tyhjäpäivien määrää, siemennysten määrää tiineyttä kohti ja tiinehtymisprosenttia. Vaihtelevat tulokset voivat johtua erilaisista koejärjestelyistä, tilastollisista analyysimenetelmistä, havaintojen määrästä (usein liian pieni hedelmällisyyden mittaamiseksi luotettavasti), kohdun terveydentilasta, lehmän iästä, poikimiskertojen määrästä, lehmien hoidosta ja ravintoaineiden saannista. Liian runsaan valkuaisruokinnan aiheuttamaan heikentyneeseen hedelmällisyyteen liittyy usein kudosten urea- ja ammoniakkipitoisuuden nousu,mikä huonontaa lisääntymiselinten fysiologista toimintaa, muuttaa hormonien eritystä tai lisää negatiivista energiatasetta poikimisen jälkeen. Vuoden 1993 tarkkailuaineistojen (16 051 karjaa) analysointi osoitti, että maidontuotannon optimi saavutettiin rehuannoksen raakavalkuaispitoisuuden ollessa 180 g/kg kuiva-ainetta (ka) hedelmällisyysparametrien pysyessä lähes ennallaan. Tutkittaessa tankkimaidon ureapitoisuuden vaikutusta hedelmällisyyteen 5 437 tilan aineistossa havaittiin, että tilojen väliset erot maidon ureapitoisuudessa eivät vaikuttaneet hedelmällisyyteen. Johtopäätöksenä voidaan todeta, että rehuannoksen raakavalkuaispitoisuuden nostaminen 150:stä 170 g:aan/kg ka lisää maidontuotantoa huonontamatta merkittävästi hedelmällisyyttä.

Associations between protein feeding and reproductive efficiency in the dairy cow are reviewed. Examination of published data indicated that reproductive responses assessed as days open, services per conception or conception rate following changes in protein feeding tend to be inconsistent. Discrepancies can arise due to between-study variations in experimental design, statistical analysis, sample population size, uterine health, cow age, parity, reproductive management or nutrient intake. Detri-mental effects on reproductive efficiency following periods of excessive protein feeding are often attributed to increases in tissue urea and ammonia oncentrations leading to impaired reproductive hysiology, modified endocrine function or exacerbated postpartum negative energy balance. Examination of data collected from Finnish dairy herds (n = 16 051) participating in the national milk recording scheme during 1993 indicated that milk production was maximised in herds fed diets containing 180 g crude protein/kg dry matter. In contrast, no consistent relationships were identified between increases in on-farm protein feeding necessary to secure higher milk production and herd reproductive efficiency assessed as calving interval, first service interval and number of inseminations per calving. Further examination of data derived from 5 437 herds within the National recording scheme indicated that on-farm reproductive efficiency was independent of large variations in the mean annual urea concentration of bulk tank milk. It is concluded that increases in the crude protein content of Finnish dairy cow rations from 150 to between 170 and 180 g/kg dry matter would allow improvements in milk production to be realised without leading to significant reductions in reproductive efficiency.
Special issue. To mark the 90th anniversary of the scientific agricultural society of Finland
Keywords: lisääntymisteho; urea; lypsykarja; märehtijät; ruokinta; rehut; valkuaisrehut; tiinehtyvyys; dairy cow; dietary protein; reproductive efficiency; urea